Complete-arch implant-supported dental rehabilitations assisted by navigated surgery: a satisfaction study - Douley J.; Boisramé S.; Guiol J. (Journal of Oral Medicine and Oral Surgery, 2025)
Purpose: to evaluate the implant survival and the prevalence of biologic and mechanical complications in edentulous patients restored with implant fixed complete dental prostheses (IFCDPs) assisted by navigated surgery, and to measure the impact on daily life of this prosthetic rehabilitation. Materials and methods: Patients restored with IFCDPs by a single experienced surgeon assisted by the X-Guide navigated surgery tool between 2019 and 2023 were selected. Outcome measures were implant cumulative survival rate (CSR), mechanical prostheses complications and the patient satisfaction was investigated using a standardized questionnaire. Results: A total of 55 patients and IFCDPs were included, totaling 290 implants on 4 mandibles and 51 maxillae. The implant CSR was 100%, no bone loss or implant failure was observed while 8 mechanical complications (15.25%) were reported, including 4 resin losses on TR group and 4 prosthetic tooth fractures in the BED group. Regarding the satisfaction questionnaire, 82% of the patients feeling more comfortable at work and/or in their social life whereas 31% had difficulties pronouncing certain words. Conclusion: This operative procedure assisted by navigated surgery presented reliable clinical outcomes with a high CSR and a high level of patient satisfaction, despite several mechanical complications.